IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK TERLANTAR PADA DINAS SOSIAL PROVINSI SULAWESI TENGAH - Sandi, Irwan (Katalogis, 2016)
This study aims at determining the extent of success of Homeless Children Protection Policy Implementation at the Social Service Office of Central Sulawesi. The type of this research is descriptive qualitative. The informants are the caretaker of Head of Department of Central Sulawesi Province, Programs Planning Section which is in charge of children, Department of Social Welfare Central Sulawesi province in charge of the child, the Vice Chairman of Commission IV DPRD Central Sulawesi that is in charge of children, the Chairman of the Children Protection Institution Central Sulawesi as NGOs that concerns about children. The data collection techniques in this research are observations, interviews, and documentations. The results of this research were analyzed by using the theory of Van Meter Van Horn that is six indicator of the success of an implementation including: 1) Basic Measures and Policy Objectives 2) Policy Resources 3) Communication among Organizations 4) Characteristics of Implementing Agencies 5) Disposition Implementor 6 ) Economy Condition, Social and Politic. The research results show that the homeless children protection policy implementation at Dinas Social of Central Sulawesi Province has not been fully successful as not all aspects are met, for axample WC is not good, bedroom is very small. especially the lack of special programs for homeless children due to lack of budget (material resources), especially the lack of special programs for homeless children due to lack of budget (material resources).